Perception of Virtual Learning Among Student Athletes: Differences by Gender and Age - Miftakhul Jannah; Rachman Widohardhono; Nurchayati; Ima Fitri Sholichah; Siti Jaro'ah (Studies in Learning and Teaching, 2023)
Aside from sports practice, student athletes are required to study on campus, sometimes learning was carried out online. Surabaya State University develops online learning and is named Virtual Learning Surabaya State University, abbreviated as Vinesa. The application of Vinesa needs to get a response from users, one of whom is a student athlete. Therefore, this study aims to determine student athlete perceptions of Vinesa. A cross-sectional approach was used in this research. A total of 125 student athletes were involved in this study (86 male, 39 female, age range of 19–24 years). The research instrument used was the Vinesa perception scale. The data analysis technique uses descriptive statistics. The calculation produces 5 categories, namely very good, good, moderate, less, and very less. The results show that majority of student-athlete perceptions of Vinesa are at a moderate level, namely 45.6%. There was no difference in perception of vinesa in the adolescent and early adult age groups also between male and female student athlete. Based on these results, the Vinesa development team needs to make improvements to the server to make it more accessible. In addition, it is necessary to complete the application usage guide so that it is easier for Vinesa users to understand.